THE ELECTRIC FIELD IN NORTHERN ENGLAND AND SOUTHERN SCOTLAND: IMPLICATIONS FOR GEOMAGNETICALLY INDUCED CURRENTS - Mckay A.J.; Whaler K.A. (My University, 2006)
Magnetotelluric (MT) data, in the form of MT tensors, are used to estimate directly the size and spatial distribution of the electric field in northern England and southern Scotland with the aim of predicting the flow of geomagnetically induced currents (GIC) in power networks in the region. MT and Geomagnetic Deep Sounding data from a number of different field campaigns, at a period of 750 s, are employed. The MT data are cast in the form of telluric vectors, which allow a joint hypothetical event analysis (HEA) of both Geomagnetic Deep Sounding and MT data. This analysis reveals qualitatively the pervasive effects of electric field distortion in the region. Two approaches are taken to understand how the spatial structure of the regional electromagnetic field is affected by local distortions, and what the origin of these distortions might be. The dimensionality, and form of electric field distortion, of the MT tensors is investigated using the Weaver et al. and Bahr classification schemes, and by examining the misfit of a galvanic distortion model as a function of rotation angle. At sites where the galvanic distortion model is found to be appropriate the regional MT tensors are recovered using tensor decomposition techniques. It is found that recovering the regional MT response reconciles the geometry of induced currents implied by the MT data with that of the Magnetic Variation anomalies. Lilley's central impedances are used to calculate rotationally invariant effective telluric responses. In the Southern Uplands the magnitude of the effective telluric response is approximately 0.25-0.5 mV km-1 nT-1, but as the Southern Uplands Fault is approached it rises steadily to 3 mV km-1 nT-1. In the Midland Valley, the effective telluric response is approximately 0.5 mV km-1 nT-1 which rises steadily to 2.5 mV km-1 nT-1 as the Southern Uplands and Highland Boundary Faults are approached to the southeast and northwest, respectively. Therefore, the increase in the magnitude of the effective telluric response correlates with the approach of a major tectonic boundary such as the Southern Uplands Fault. These results show that the induced electric field strength varies considerably throughout the central Scotland region. In addition, the HEA indicates that due to lateral changes in conductivity structure the direction of the electric field deviates significantly from the regional direction implied by the polarization azimuth of the primary geomagnetic induction. Therefore, any attempts to model the flow of GIC in the region need to account for the spatial variation of both the magnitude and azimuth of the electric field. © 2006 Natural Environment Research Council Journal compilation © 2006 RAS.
Keywords: DISTORTION ANALYSIS; ELECTROMAGNETIC INDUCTION; ELECTROMAGNETIC MODELLING; GEOMAGNETICALLY INDUCED CURRENTS; MAGNETOTELLURICS; MAGNETOVARIATION